Prototype and methodology for the characterization of the polymer-calibrator interface heat transfer coefficient - Carneiro, O. S. (2013)
The extrusion of technical thermoplastics profiles generally uses a dry calibration/cooling system, composed by one or several calibrators in series. One of the major difficulties to be faced when modelling this important stage is an adequate prescription of the heat transfer coefficient, hinterface, between the plastic profile surface and the cooling medium, which must include the effect of the interface contact resistance. This is the motivation that led the present research team to develop a prototype calibration system and respective methodology for the characterization of hinterface values which is able to consider a variety of conditions that can be found in extrusion practice. A modular construction was adopted for the calibration system, which allows studying easily the effect of several process parameters. In this work, the developed prototype system is described and its use is illustrated in the determination of hinterface for the production of a polystyrene tape, under specific processing conditions.